(untitled) (Applied Biological Research, 2018)
The seeds of Nemesia strumosa were packed in five different packaging (cloth bag in desiccator, plastic bin, polyethylene bag [600 gauze], cloth bag and aluminum foil pack) and stored in three storage chambers viz., cold storage (0-4°C and 90±2.7% RH), incubator (20-22°C and 75±1.5% RH) and ambient conditions for 18 months from May 2015 to October, 2016. The seed germination and seed viability were monitored at monthly interval from every packaging and storage chamber in three replications of 100 seed each. The seeds kept in cold storage depicted significantly higher germination (28.6%). The results revealed that seed germination remained above 90% during the initial four months of storage, which decreased gradually to 82.6% after five months in November. Maximum seed germination was recorded from aluminum foil pack (27.5%). The seed stored in cold store either in aluminum foil or desiccator showed germination upto 12 months while cloth bags gave least germination, irrespective of storage temperature. Maximum seed viability (30.5%) was recorded in cold store, followed by ambient storage (26.1%) for 18 months. The storage in desiccator maintained maximum viability (28.8%) which was at par with aluminum foil (28.4%) after 18 months of storage.